ANALISIS IMPLEMENTASI PRINSIP CHARACTER, CAPACITY, CAPITAL, COLLATERAL, CONDITION OF ECONOMIC, DAN SHARIA DALAM UPAYA PENCEGAHAN PEMBIAYAAN MURABAHAH BERMASALAH DI KSPPS BMT NURUL BAROKAH CABANG SAMBI - Muhammad Kusaini; Heny Kurnianingsih (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
Optimism about the Islamic economic system can be utilized by Muslim scholars to build institutions engaged in finance, including Baitul Maal Tamwil (BMT). BMT has two working areas, Baitul Maal and Baitut Tamwil. There is a growing belief that the Islamic economic system can be the answer to the challenges of an increasingly complex era. This study uses a quantitative approach that is carried out online using a google form to compile a questionnaire as the basis for making a survey in order to obtain data. The sampling technique used purposive sampling with the number of respondents who obtained 277 financing members from the Sharia Savings and Loans Cooperative (KSPPS) BMT Nurul Barokah in the Sambi branch. The test results show that the variables of character, capacity, capital and condition of economic partially affect the Prevention of Troubled Murabahah Financing. Meanwhile, the collateral and sharia variables must be improved in the analysis of collateral transactions and sharia analysis so that the business being financed is truly a business that does not violate sharia.